Correlation of Process Parameters with Mechanical Properties of Laser Sintered PA12 Parts. (28th February 2017) - Hofland, Eva C.; Baran, Ismet; Wismeijer, Dagmar A.
Abstract : Selective laser sintering (SLS) is an additive manufacturing technique that enables the production of customized, complex products. SLS has proven itself a viable prototyping tool and production method for noncritical products. The industry has picked up on the potential of SLS, which raised the question whether it is possible to produce functional products with reproducible mechanical properties for application in critical sectors. Properties of SLS parts highly depend on the applied process settings. Hence, present work examined the influence of key process parameters (preheating temperature, laser power, scan spacing, scan speed, layer thickness, and part build orientation) on the properties (tensile strength, tensile modulus, elongation at break, and part density) of SLS produced parts. A design of experiments (DoE) approach was used to plan the experiments. Test samples according to DIN EN ISO 527-2 were produced on a sintering system (EOSINT P395) using polyamide 12 powder (EOS PA2200). Regression models that describe the relation between the process settings and resulting part properties were developed. Sensitivity analysis showed that mechanical properties of sintered parts were highly affected by layer thickness and scan spacing variations.